Phraseological Units In English And Their Equivalents In Uzbekistan - Uktamova, Mokhigul; Muhammadov, Akmaljon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines phraseological units in the English language and their equivalents in the Uzbek language. The study analyzes various English phraseological expressions and identifies their corresponding equivalents in Uzbek. It also highlights the challenges that arise in translating phraseological units, particularly the limitations of literal translation, which does not always convey the intended meaning. The article discusses the semantic features of phraseological units, their usage in speech, and their cultural aspects. The results of the research are significant for identifying phraseological correspondences between English and Uzbek and for improving the effectiveness of the translation process.